2018
DOI: 10.4103/abr.abr_279_16
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Seizure Frequency Distribution in Epileptic Patients with Normal and Abnormal Electroencephalogram in Al-Zahra Hospital of Isfahan

Abstract: Background:Epilepsy is a chronic neurological disorder characterized by seizure recurrence in patients. Electroencephalogram (EEG) has a diagnostic and prognostic role in the management of patients. Studies have shown a significant relation between seizure recurrence and abnormal EEG in newly diagnosed epileptic patients, and people with first episode of unprovoked seizure. The aim of this study is to evaluate seizure frequency in chronic epileptic patients on drug therapy based on normal or abnormal EEG.Mater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 27 publications
0
2
0
1
Order By: Relevance
“…grubu arasında da nöbet tekrarı açısından anlamlı bir fark olmadığı gözlenmiştir. [8] Bizim çalışmamıza benzer sonuç elde edilen bir çalışmada ise yüksek ve düşük İED sıklığı ile nöbet sıklığı arasında anlamlı bir ilişki saptanmamıştır. [3] 2001 yılında yapılan bir diğer çalışmanın sonuçları çalışmamızı destekler niteliktedir.…”
Section: Discussionunclassified
“…grubu arasında da nöbet tekrarı açısından anlamlı bir fark olmadığı gözlenmiştir. [8] Bizim çalışmamıza benzer sonuç elde edilen bir çalışmada ise yüksek ve düşük İED sıklığı ile nöbet sıklığı arasında anlamlı bir ilişki saptanmamıştır. [3] 2001 yılında yapılan bir diğer çalışmanın sonuçları çalışmamızı destekler niteliktedir.…”
Section: Discussionunclassified
“…Compared with ordinary tissue regeneration materials, nerve regeneration materials need to satisfy more requirements, including guided axons, sufficient strength to oppose tensile movement, and favorable electric conductivity that promotes cell adhesion, proliferation, and infiltration. [ 141 ] Electrospun nanofibers have become increasingly popular for the production of nanofibrous scaffolds in nerve regeneration because of their flexibility, large specific surface area, and cost‐effectiveness. [ 69 ]…”
Section: Promoting Biological Processes For Accelerating Tissue Regenmentioning
confidence: 99%
“…found that aligned PHB/15% CTS nanofibers displayed better tensile strength compared with random PHB/CTS (15%) scaffolds, due to the orientation of the electrospun fibers. [ 141 ] The ECM tensile strength provided axons with excellent viability to adhere and extend, which meant the suitable morphology contributed to nerve regeneration. Moreover, Gnavi et al.…”
Section: Promoting Biological Processes For Accelerating Tissue Regenmentioning
confidence: 99%